2014
DOI: 10.1111/bph.12966
|View full text |Cite
|
Sign up to set email alerts
|

Spinal blockage of P/Q‐ or N‐type voltage‐gated calcium channels modulates functional and symptomatic changes related to haemorrhagic cystitis in mice

Abstract: BACKGROUND AND PURPOSESpinal voltage-gated calcium channels (VGCCs) are pivotal regulators of painful and inflammatory alterations, representing attractive therapeutic targets. We examined the effects of epidural administration of the P/Q-and N-type VGCC blockers Tx3-3 and Phα1β, respectively, isolated from the spider Phoneutria nigriventer, on symptomatic, inflammatory and functional changes allied to mouse cyclophosphamide (CPA)-induced haemorrhagic cystitis (HC). The effects of P. nigriventer-derived toxins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…Furthermore, the activation of voltage‐gated calcium 3.2 T‐type channels is related to bladder pain and referred hyperalgesia in mice with cyclophosphamide‐induced cystitis . P/Q‐type and N‐type voltage‐gated calcium channels are involved in nociceptive and inflammatory events .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the activation of voltage‐gated calcium 3.2 T‐type channels is related to bladder pain and referred hyperalgesia in mice with cyclophosphamide‐induced cystitis . P/Q‐type and N‐type voltage‐gated calcium channels are involved in nociceptive and inflammatory events .…”
Section: Discussionmentioning
confidence: 99%
“…This proposal is further supported by previous findings showing that TRPA1 mediates sustained hyperalgesic responses in different models [ 14 , 27 ]. Indeed, it has been demonstrated that spinal blockage of the N-type and P/Q-type VGCC (voltage-gated calcium channel) could attenuate inflammatory and nociceptive events associated with cystitis [ 10 ]. Consistent to this notion, TRPA1 located on DRG contributes to the transmission of nociceptive information to second-order neurons in the spinal dorsal horn [ 14 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main syndrome of acute cystitis is urinary frequency, urgency and dysuria in addition to the impairment of patient quality of life. Chemical cystitis is the key adverse effect observed with cyclophosphamide (CY) chemotherapy, and it results from the formation of acrolein, which is a known agonist of TRPA1 [ 9 , 10 ]. The TRPA1 channel has been suggested to mediate mechanical and nociceptive sensitivity in both physiological and pathological states of the lower urinary tract [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, these toxins have different antinociceptive effects when compared with ω‐CTx‐MVIIA, which have been explained due to diverse actions on N‐type VGCC or due to inhibition on other VGCC such as R‐type, P/Q‐type and L‐type . In addition, Phα1β and CTK 01512‐2 have shown antagonism on TRPA1 channels, besides acting on VGCC, which may increase not only their antinociceptive effects, but also their adverse reaction . Otherwise, ω‐CTx‐MVIIA is a selective and reversible blocker of the N‐type VGCC, preventing calcium influx .…”
Section: Resultsmentioning
confidence: 99%
“…N‐type VSCC are widely found in spinal cord neurons and control the release of neurotransmitters, playing an important role in the ascending peripheral pain to the brain . Some studies have shown that Phα1β toxin has antinociceptive action in several rodent pain models, showing effects on acute and persistent pain, including visceral, neuropathic, inflammatory, surgical and cancer pains …”
Section: Introductionmentioning
confidence: 99%